(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This paper aims to examine Indonesia’s space command initiative by developing a normative legal reasoning based on the national resilience framework, specifically the integration of Astagatra and legal hierarchy to support space defence regulation. Study Design/Methodology/Approach: The research applies normative legal analysis using statutory sources including the 1945 Constitution and Law Number 34 Year 2004. The principle of legal supremacy guides the interpretation of legislative gaps. Astagatra is used as an interdisciplinary framework to assess whether legal norms reflect national resilience objectives in space command development. Findings: The current legal framework lacks specific regulation for space command. However, the Astagatra-based legal reasoning model demonstrates normative coherence and strategic relevance in positioning space command within Indonesia’s defence architecture. The integration of constitutional norms and resilience dimensions supports the urgency for legislative reform. Originality/Value: This paper contributes a legal reasoning framework that combines statutory authority with a resilience-based policy model. It offers a strategic justification for regulating space command as a national priority aligned with long-term state resilience.